Unveiling Students’ Perceptions of Effective Physics Instruction (Pragyaratna प्रज्ञारत्न, 2023)
The main aim of this study was to explore secondary school students' perceptions of successful physics education and learning. The researchers employed a descriptive survey approach to attain this goal. A total of 55 tenth-grade students from two public schools in the Kathmandu and Lalitpur districts participated in the study. The researcher constructed a structured Likert-type questionnaire with a 4 -point scale as the instrument for collecting data. The reliability coefficient was calculated using Cronbach alpha and, following the instrument’s validation, was revealed to be 0.84. The researcher used forms for questionnaires, and to assure 100 percent return, the questionnaires were then collected. The data was evaluated by the researchers by computing the mean, doing frequency distribution analysis, and determining the percentage of student replies for each item. In addition, the findings were compiled and gathered in order to answer the study question. The majority of students have a weak foundation in physics, according to some findings.